Peningkatan Efisiensi Manpower Berdasarkan Prinsip Shoujin di Area Produksi Head Lamp PT Astra Otoparts Divisi Adiwira Plastik - Sanjaya, Robert Gorevi; Palit, Herry Christian (Jurnal Titra, 2013)
Regional Minimum Wage (RMW) enhancement in Kab. Bogor is adequately high which in 2013, the RMW increasing 61% from 2012. RMW enhancement which not followed with manpower (MP) efficiency could became a disadvantage for company. The initial condition evaluation indicate the MP efficiency value is 45% and the line efficiency value is 70,5%. Total initial manpower allocation is 8 MP. Improvement executed which consider to customer demand and production capability. Evaluation result indicates thereâs unbalance work load distribution of each MP. Improvement planned such as balancing the work load of each MP, machine modification, and re-layout the production area. The implementation based on shoujin principleâs resulted manpower saving from 8 MP to 6 MP, which the MP efficiency value is 53% and the line efficiency value is 85,8%. Standardized work did as well as the control item in order to stabilize the improvement process. The next step is the analysis of production capability to face the increasing of customer demand. This analysis concluded that production needed additional overtime and additional work shift (for November only) in order to fulfill the customer demand.